Testing behavior and effects of PRVs and RTC valves during hydrant activation scenarios. Issue 3 (16th March 2018) - Creaco, E.; Campisano, A.; Modica, C.
Abstract: This paper provides an insight into behavior and effects of pressure reducing valves (PRVs) and of valves controlled in real time (RTC) during hydrant activation scenarios, which determine high-flow conditions in water distribution networks (WDNs). The analysis is carried out through the pressure-driven unsteady flow modeling of an Italian WDN, in which a pressure control device is assumed to be installed in the pipe outgoing from the source. Scenarios are constructed considering alternatively a PRV or an RTC valve, as pressure control device, and two different sites for hydrant activation. The results highlight that, thanks to its capability of controlling the service pressure at the critical node, the RTC valve performs better than the PRV, which is regulated based on its outlet pressure. In fact, the adoption of the RTC valve attenuates pressure deficits in the network, above all when the control time step is suitably small to attenuate pressure head oscillations at the controlled node. An additional benefit of RTC lies in increased outflows from the hydrant. The benefits of the RTC valve are smaller when the hydrant is activated in more redundant parts of the network, where pipe water discharge variations put the system to a less severe test.